2016
DOI: 10.3402/fnr.v60.31871
|View full text |Cite
|
Sign up to set email alerts
|

Skin photoprotective and antiageing effects of a combination of rosemary (Rosmarinus officinalis) and grapefruit (Citrus paradisi) polyphenols

Abstract: BackgroundPlant polyphenols have been found to be effective in preventing ultraviolet radiation (UVR)-induced skin alterations. A dietary approach based of these compounds could be a safe and effective method to provide a continuous adjunctive photoprotection measure. In a previous study, a combination of rosemary (Rosmarinus officinalis) and grapefruit (Citrus paradisi) extracts has exhibited potential photoprotective effects both in skin cell model and in a human pilot trial.ObjectiveWe investigated the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 62 publications
0
38
0
2
Order By: Relevance
“…Other studies based on procyanidin-based polyphenolic extracts provided conclusive results on the inhibition of UV-induced age spots due to the high number of subjects utilised [ 92 ]. The efficacy of rosemary and citrus polyphenols to reduce skin redness and MED and to improve skin elasticity and decrease wrinkle depth in correlation to a decrease in skin lipid oxidation was also consistently proven [ 96 ], and a mechanistic rationale was also provided in skin cell model [ 95 ]. A red orange extract enriched in anthocyanins [ 97 ] and Polypodium leucotomos extract [ 98 , 99 ] also exhibited evidence of improvement in several skin signs related to photo-aging (erythema, hydration, elasticity and pigmentation), but with a much lower number of subjects, which compromises the consistency of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies based on procyanidin-based polyphenolic extracts provided conclusive results on the inhibition of UV-induced age spots due to the high number of subjects utilised [ 92 ]. The efficacy of rosemary and citrus polyphenols to reduce skin redness and MED and to improve skin elasticity and decrease wrinkle depth in correlation to a decrease in skin lipid oxidation was also consistently proven [ 96 ], and a mechanistic rationale was also provided in skin cell model [ 95 ]. A red orange extract enriched in anthocyanins [ 97 ] and Polypodium leucotomos extract [ 98 , 99 ] also exhibited evidence of improvement in several skin signs related to photo-aging (erythema, hydration, elasticity and pigmentation), but with a much lower number of subjects, which compromises the consistency of the results.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 weeks of product consumption, results showed decreasing wrinkle depth and increasing elasticity at 100 and 250 mg extracts dose regimens. At 2 weeks of product use, results showed decreasing wrinkle depth and increasing elasticity at 100 and 250 mg extracts dose regimen [ 96 ]. In this second study, number of subjects was high and statistically significant differences were confirmed in MED and also in wrinkle depth, elasticity and skin lipoperoxides between placebo and intervention groups.…”
Section: Bioactive Botanical Extractsmentioning
confidence: 99%
“…Citrus contains a large amount of flavonoids, and rosemary is rich in polyphenols and diterpenes. In humans, oral administration of a combination of citrus and rosemary extracts decreased sensitivity to erythema induced by UVR, as quantified by an increased MED that after 8 weeks of treatment ranged from 34% in Perez-Sanchez's study ( 85 ) to 29.8% in Nobile's study ( 86 ).…”
Section: Dietary Botanicals (Table 3 )mentioning
confidence: 96%
“…Grapefruit is rich in phenolic compounds, among which gallic acid (GA) is the most abundant (Nobile et al 2016). In a study conducted by Pérez-Sánchez and colleagues cultivation of human keratinocytes, prior to UVB irradiation, in the presence of grapefruit extract alone (12.5–100 µg/mL) or in combination with rosemary extract (12.5–100 µg/mL), which is also rich in GA, was investigated.…”
Section: Plant Extracts Used Against Uvb-induced Photodamagementioning
confidence: 99%